First detection of Leishmania major DNA in Sergentomyia (Spelaeomyia) darlingi from cutaneous leishmaniasis foci in Mali. - Zohra Berdjane-Brouk (Public Library of Science (PLoS), 2012)
Background Leishmania major complex is the main causative agent of zoonotic cutaneous leishmaniasis (ZCL) in the Old World. Phlebotomus papatasi and Phlebotomus duboscqi are recognized vectors of L. major complex in Northern and Southern Sahara, respectively. In Mali, ZCL due to L. major is an emerging public health problem, with several cases reported from different parts of the country. The main objective of the present study was to identify the vectors of Leishmania major in the Bandiagara area, in Mali. Methodology/principal findings An entomological survey was carried out in the ZCL foci of Bandiagara area. Sandflies were collected using CDC miniature light traps and sticky papers. In the field, live female Phlebotomine sandflies were identified and examined for the presence of promastigotes. The remaining sandflies were identified morphologically and tested for Leishmania by PCR in the ITS2 gene. The source of blood meal of the engorged females was determined using the cyt-b sequence. Out of the 3,259 collected sandflies, 1,324 were identified morphologically, and consisted of 20 species, of which four belonged to the genus Phlebotomus and 16 to the genus Sergentomyia. Leishmania major DNA was detected by PCR in 7 of the 446 females (1.6%), specifically 2 out of 115 Phlebotomus duboscqi specimens, and 5 from 198 Sergentomyia darlingi specimens. Human DNA was detected in one blood-fed female S. darlingi positive for L. major DNA. Conclusion Our data suggest the possible involvement of P. duboscqi and potentially S. darlingi in the transmission of ZCL in Mali.